Characterization of collagen profile in peritoneal metastases of colorectal cancer - P. Villarejo-Campos; S. García Gómez-Heras; S. González-Moreno; S. Qian Zhang; R. Franco-Rodríguez; I. Díaz-Caro; R. Olivera-Salazar; D. García-Olmo; M. García-Arranz (Scientific Reports)
Abstract The tumor microenvironment (TME) plays a critical role in cancer progression and response to treatment. In colorectal cancer (CRC), a collagen-rich extracellular matrix (ECM) is a well-established feature of primary tumors and liver metastases. However, the composition of the ECM in peritoneal metastases remains poorly characterized. In this descriptive study, we analyzed the histological distribution of four major collagen types (I, II, III, and IV) in peritoneal metastases from 39 CRC patients using immunohistochemical techniques. Type III fibrillar collagen was predominant, showing moderate to high expression in 80 percent of cases, followed by type IV collagen in 56 percent. Type I collagen demonstrated low intensity in 64 percent of cases. Notably, type II collagen, typically restricted to cartilaginous tissues, was also detected within the tumor stroma, an unexpected finding given its usual absence in this histological contex. These results highlight the unique collagen-rich stroma in CRC peritoneal metastases, dominated by types III and IV collagen, and identify type II collagen as a novel component. This study provides new insight into the stromal architecture of CRC peritoneal metastases and may serve as a foundation for future research on collagen-targeted therapeutic strategies.